Brok nad Bugiem – pałac biskupów płockich. Badania wykopaliskowe 1983-1984 roku - Gula, Jerzy (Acta Universitatis Lodziensis. Folia Archaeologica, 2001)
The paper describes the results of architectural and archaeological researches in the palace of Płock bishops in Brok. In the preface the author presents the history of the object till the year 1909 when the inventory plan was accomplished. In the years 1983-1984, on initiative of the Provincial Conservator of Monuments in Ostrołęka, the ruins of the palace were subjected to archaeological examinations. The main objective of the works was to verify the hypothesis about early Mediaeval or Mediaeval provenance of the object. It was also planned to define the character and possibly the shape of the first, known from the sources, original construction from the beginning of the 17th century. Besides it was intended to define the range of damages caused by the Swedes in the times of Swedish wars and to check how far the remaining ruins were later adapted for the needs of the 18th century building. Finally, in connection with the project to use this object in the form of a stable ruin it seemed justified to make an attempt to reveal its plan until the state from the year 1909.